Pelatihan Microsoft Excel bagi Guru-guru di SD Negeri 3 Bareng Lor Klaten - Kurnianingtyas, Chandra Dewi; Ratna Mustika Dewi (Jurnal Atma Inovasia, 2023)
SD Negeri 3 Bareng Lor Klaten is an elementary school located in the North Klaten area. Adequate facilities are needed in presenting the right learning facilities for students. The right resources will help in the teaching and learning process in an institution, especially in school units. One of the resources to be aware of is the "Teacher" itself. The quality of a teacher will greatly affect the quality of teaching and learning in a school. Fun and capable teachers will be able to increase students' interest in participating in learning at school. The ability of a teacher to analyze students is very necessary in the teaching and learning process. One of the tools that can be used is to use Microsoft Excel in analyzing statistically about student data or school data. Microsoft Excel is a program or application that is part of the Microsoft Office installation package, functioning to process numbers using a spreadsheet consisting of rows and columns to execute commands. One of the benefits that can be utilized by teachers from SD Negeri 03 Bareng Lor Klaten schools when gaining knowledge about advance excel is that it can provide interesting visualizations for teachers and students at school. Based on the above conditions, a Microsoft excel training is needed which is intended for teachers who are at SD Negeri 3 Bareng Lor Klaten. The expected goal is that teachers can have more mastery with the use of Microsoft excel so that they can provide more attractive visual exposure to students or parents. The methods used in the training are face-to-face methods, interviews, and discussions. The material given during the training is an introduction to excel, data management, creating tables and graphs, exercises of basic formulas and formulas, filtering and sorting data. Microsoft Excel training for teachers at SD Negeri 3 Bareng Lor Klaten can be carried out properly.